2021
DOI: 10.3390/pharmaceutics13122171
|View full text |Cite
|
Sign up to set email alerts
|

Dose Finding and Food Effect Studies of a Novel Abiraterone Acetate Formulation for Oral Suspension in Comparison to a Reference Formulation in Healthy Male Subjects

Abstract: Currently approved formulations of the androgen synthesis inhibitor abiraterone acetate (AA) consist of multiple tablets administered daily in a fasted state. Removing the food effect and switching to a suspension formulation is expected to improve the pharmacokinetic profile and facilitate drug administration for patients with late-stage prostate cancer. Two four-sequence, four-period randomized crossover investigations were undertaken to establish the pharmacokinetic profiles of single doses of commercially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…5,6 In line with previous studies, prandial status showed extensive effects on the PK of ABI in a Chinese population. It was also reported that fed condition increased C max of ABI in multiple races by 2.2 to 16.8-fold and AUC by 2.0 to 9.7-fold relative to those in fasted condition, [21][22][23][24][25][26][27][28][29][30] respectively. Such discrepancy in the fold change for systemic exposure might be due to the different ethnicity and distinct food composition.…”
Section: Discussionmentioning
confidence: 84%
“…5,6 In line with previous studies, prandial status showed extensive effects on the PK of ABI in a Chinese population. It was also reported that fed condition increased C max of ABI in multiple races by 2.2 to 16.8-fold and AUC by 2.0 to 9.7-fold relative to those in fasted condition, [21][22][23][24][25][26][27][28][29][30] respectively. Such discrepancy in the fold change for systemic exposure might be due to the different ethnicity and distinct food composition.…”
Section: Discussionmentioning
confidence: 84%